Sonographic features of trisomy 13 at midpregnancy - Tongsong T. (2014)
Objectives: To evaluate the sonographic characteristics, at 16-22 weeks of gestation, of fetuses later diagnosed with trisomy 13. Methods: This descriptive analysis of a case series was conducted from June 1989 to May 2001 at the Department of Obstetrics and Gynecology, Faculty of Medicine, Chiang Mai University, Thailand. Women with abnormal sonographic findings at midpregnancy (16-22 weeks of gestation) underwent amniocentesis or cordocentesis for karyotyping, and the inclusion criterion was proven trisomy 13. Results: Indications for sonographic examination at midpregnancy were a genetic risk, large- or small-for-date fetus, and other suspected anomalies. Fifteen fetuses were later diagnosed with trisomy 13. In all of these cases there was at least one abnormal sonographic finding. In only one case did the fetus show no structural abnormality (at 17 weeks), but polyhydramnios and fetal growth restriction were observed. Common sonographic findings included holoprosencephaly with associated facial anomalies, and abnormal feet and/or hands, especially polydactyly. Non-structural abnormal findings such as polyhydramnios or fetal growth restriction were seen in less than one third of the fetuses. Conclusions: Nearly all the fetuses with trisomy 13 had sonographic characteristics of abnormalities at midpregnancy although common findings had often not yet appeared or the findings were low-sensitive. Detailed ultrasound at midpregnancy could effectively screen for further genetic testing pregnancies at risk for trisomy 13. © 2002 International Federation of Gynecology and Obstetrics.